Nebulizer induced superinfection and sepsis with Chryseobacterium indologenes in a postoperative patient with Acinetobacter baumannii pneumonia: a case report and review - Padmaja, Kanne; Lakshmi, Vemu; Sreekanth, Yelliboina; Gopinath, Ramachandran (International Journal of Infection Control, 2012)
Chryseobacterium indologenes, a non-fermentative Gram-negative bacillus, is an uncommon pathogen in humans causing a variety of invasive infections, especially in hospitalized patients with severe underlying disease with indwelling devices. We herein report a case of superinfection and sepsis caused by C. indologenes, in a postoperative patient being managed in the respiratory intensive care unit (RICU) for acute respiratory distress syndrome and Acinetobacter baumannii infection. C. indologenes was probably acquired from an ultrasonic nebulizer used for colistin aerosolization against A. baumannii. Subsequently the patient developed superinfection and sepsis due to C. indologenes. The patient had a favourable response to a prolonged therapy with Fluoroquinolones and Trimethoprim sulfamethoxazole.